Study of fetomaternal outcome in second stage caesarean section - Goswami, Kamal D.; Parmar, Manisha M.; Kunjadiya, Avnika N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The incidence of second stage caesarean section is more in developing countries. Caesarean sections done at full cervical dilatation with impacted fetal head are difficult and associated with an increased incidence of maternal and fetal complications. Methods: This was prospective observational study conducted at a tertiary teaching institute. All second stage caesarean sections performed between September 2017 to August 2018 were analysed in terms of incidence, indications of caesarean-section, intra-operative and postoperative complications, maternal and fetal outcome. Results: During the study period there were total 7270 deliveries. Out of this 1884 deliveries were done by caesarean section. Out of them 50 were 2nd stage caesarean sections contributing to 2.65% of total sections. Patwardhan method was used in 50% cases for deliveryof deeply engaged head. Intra-operative complications were higher in terms of atonic pph (8%), extension of uterine incision (16%), in 3 cases bladder injury was noticed. Obstetric hysterectomy was required in 4% cases. 14% cases had postoperative febrile illness and 8% cases had wound infection. 44% babies required NICU admissions and neonatal death was 18%. Conclusions: Caesarean section in the 2nd stage of labour is associated with significantly increased maternal morbidity. Neonatal morbidity and mortality also increases. A proper judgement is required by a skilled obstetrician to take a decision for caesarean section at full cervical dilatation.